An anterior neurovascular interval approach to coronal shear fractures of the distal humerus: a prospective clinical study with short- to mid-term follow-up - Yang,Xiao-Hua (2019)
SUMMARY OBJECT: To explore the treatment effect of the anterior medial neurovascular interval approach to coronal shear fractures of the distal humerus. METHODS: This prospective study included two female patients who were 30-64 years old, with a mean age of 47 years. Fractures were caused by falling from a bicycle. The time between the injury and operation was 1-2 days, with a mean time interval of 1.5 days. Two patients with coronal shear fracture of the distal humerus were treated with open reduction and internal fixation using anterior neurovascular interval approach. RESULTS: There were no intraoperative and postoperative neurological and vascular complications or infections, and the fracture was united. At 12 months after the surgery, the patient returned to work without pain, and with a normal range of motion for elbow and forearm rotation. The X-rays revealed excellent fracture union, no signs of heterotopic ossification, and no traumatic arthritis. According to Mayo's evaluation standards for elbow function, a score of 100 is excellent. CONCLUSIONS: The application of the anterior neurovascular interval approach of the elbow in the treatment of shear fracture of the articular surface of the distal humerus, particularly the trochlea of the humerus, can reduce the stripping of the soft tissue.